EFFECTS OF RESISTANCE AND MULTICOMPONENT TRAINING ON BODY COMPOSITION AND PHYSICAL FITNESS OF INSTITUTIONALIZED ELDERLY WOMEN. Issue 10 (10th June 2013) - Sousa, Nelson; Mendes, Romeu; Silva, Sandro; Garrido, Nuno; Abrantes, Catarina; Reis, Victor
Abstract : Background: Physical fitness is an important indicator of health and quality of life in all population groups, and particularly in institutionalized elderly. In contrast, increased fat mass is associated with poor physical fitness and an increase in cardiovascular risk. The purpose of this study was to compare the effects of two short-term training programs on body composition and physical fitness in institutionalized elderly women. Methods: Thirty-two women (aged 72.9±6.6 years) from three institutions of the north of Portugal, were randomly assigned into a resistance training group (n=12), a multicomponent training group (n=10), and a control group (n=10). Before and after training, body mass index, waist circumference, body fat mass, fat-free mass, and six independent physical fitness tests (back scratch, chair sit-and-reach, 30-s chair stand, arm curl, 8-foot up-and-go and 6-min walk) were assessed. Both training programs consisted of two weekly sessions during 12 weeks and were planned for moderate intensity (perceived exertion of 12–13 points on Borg scale, and a range on 50–69% of one repetition maximum). The resistance training protocol included leg press, leg extensions and curls, chest press, lateral pull-down, overhead press, arm curls and abdominal exercises. The multicomponent training protocol included aerobic exercise (walking and dancing), muscular endurance exercises (using elastic bands and free weights), balance and flexibility exercises. Two-way ANOVA with repeated measures was used to examine the effects of training programs. Results: ANOVA indicated a significant main effect of group (p=0.000) for all physical fitness tests, with significant differences between both training groups and control. There were no differences between resistance training and multicomponent training. ANOVA also identified a significant main effect of time for 30-s chair (p=0.000), arm curl (p=0.002) and 6-min walk (p=0.000) in both training groups (baseline vs post-test). No significant changes were observed in body mass index, waist circumference, body fat mass and fat-free mass. Conclusions: The data suggest that 12 weeks of multicomponent training were so effective in increasing physical fitness in institutionalized elderly, as resistance training. Further, multicomponent training demonstrated a wide practical applicability, and low cost development, unlike resistance training resources that need more expensive and complex logistics in such institutions. In contrast, 12 weeks of either resistance or multicomponent moderate training were not enough to induce changes in body composition.